A continuous-wave method for sound speed measurement based on an infinite-echo model. (15th May 2022) - Salvi, Nilesh; Tan, Jinglu
Highlights: Analytical model forming basis for a method to measure sound speed. Creative use of persistent echoes giving outstanding signal-to-noise ratio. Example applications illustrating the use and usefulness of the developed method. Abstract: This paper presents a method for sound speed measurement accounting for the infinite number of echoes of a continuous wave generated between an excitation and a receiving transducer. An infinite-echo model was developed for the output signal sensed by the receiving transducer. From the model, the amplitude of the output signal is shown to be a wave (the amplitude wave) with a periodicity dependent on sound speed, excitation frequency, and pathlength. This yields a method for sound speed measurement. The method was implemented and experimentally demonstrated. Effects of medium material, transducer property, excitation frequency, and pathlength were shown and analyzed for enhancing measurement robustness. Measurement of varied materials showed a high level of consistency with known values or expected variations. More importantly, outstanding signal-to-noise ratios were observed. The method can be used in different fields. Example applications were presented to illustrate the use and usefulness of the method.